Correlation Between APGAR Scores and the Incidence of Hyperbilirubinemia in Neonates at Wangaya Regional General Hospital, Denpasar - Putri Widyastiti, Ni Nyoman; I Wayan Bikin Suryawan; Anak Agung Made Sucipta (HM Publisher, 2024)
Background: Hyperbilirubinemia is defined as total serum bilirubin level at ≥ 5 mg/dl. In Indonesia, the prevalence of jaundice is 13,7-85%. One of the risk factors for hyperbilirubinemia in neonates is babies born with a history of asphyxia. The diagnosis of asphyxia can be enforced by the APGAR scoring system. This study aims to determine the relationship between APGAR values and the incidence of hyperbilirubinemia in neonates treated at Wangaya Regional General Hospital. Methods: This research is an analytic observational study using a cross-sectional approach, which was carried out in April-May 2022. The sample was taken by consecutive sampling. Bivariate analysis was performed using the chi-square test. Confounding variables will be controlled by design and by analysis. Influential risk factors were analyzed multivariate with logistic regression. Data were analyzed with SPSS software. Results: From 84 samples, 67, 9% had hyperbilirubinemia. The 1-minute APGAR score (P = 0,017, OR = 8,373, 95% CI; 1,468 – 47,738) and the 5-minute APGAR score (P = 0,034, OR =8,680, 95% CI; 1,172 – 64, 293) had significant correlation with the incidence of hyperbilirubinemia in neonates treated at Wangaya Regional General Hospital. Conclusion: Low APGAR scores have a significant correlation with the incidence of hyperbilirubinemia in neonates treated at Wangaya Regional General Hospital. The factor that most influences the incidence of hyperbilirubinemia is the 1-minute APGAR score. Neonates born with a low 1-minute APGAR score are 8,3 times at risk of experiencing hyperbilirubinemia.